1983
DOI: 10.1093/infdis/148.3.369
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Neisseria meningitidis with Human Nasopharyngeal Mucosa: Attachment and Entry into Columnar Epithelial Cells

Abstract: The mechanisms by which Neisseria meningitidis establishes a carrier state or invades mucosal surfaces of the host to cause septicemia and meningitis are unknown. An experimental model of human columnar nasopharyngeal tissue in organ culture was developed, and the interaction of encapsulated, piliated N meningitidis with this mucosal surface was studied. Electron microscopic studies showed that meningococci attached selectively to nonciliated columnar cells of the nasopharynx. After attachment, the microvilli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
112
0
4

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(124 citation statements)
references
References 19 publications
8
112
0
4
Order By: Relevance
“…The use of sodium taurocholate to kill extramucosal bacteria is reasonable ; compared with other bile salts, sodium taurocholate has a low pK a and requires specialized active transport for efficient penetration of epithelial cells (Shiau, 1987). Invasion of nasopharyngeal explants by N. meningitidis is an active process of parasitedirected endocytosis (Stephens et al, 1983 ;Read et al, 1995). During this process, bacteria are enveloped by microvillous extensions from the cell surface, a process requiring host cell cytoskeletal rearrangement, which in turn requires polymerization of actin filaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of sodium taurocholate to kill extramucosal bacteria is reasonable ; compared with other bile salts, sodium taurocholate has a low pK a and requires specialized active transport for efficient penetration of epithelial cells (Shiau, 1987). Invasion of nasopharyngeal explants by N. meningitidis is an active process of parasitedirected endocytosis (Stephens et al, 1983 ;Read et al, 1995). During this process, bacteria are enveloped by microvillous extensions from the cell surface, a process requiring host cell cytoskeletal rearrangement, which in turn requires polymerization of actin filaments.…”
Section: Discussionmentioning
confidence: 99%
“…Meningococci attach selectively to non-ciliated columnar cells, and during this process microvilli of non-ciliated cells elongate and surround the organisms. Meningococci appear to undergo parasite-directed endocytosis and are observed in subepithelial tissues adjacent to lymphoid tissue after prolonged incubation (Stephens et al, 1983), though this is observed in a minority of explants (Read et al, 1995). Pili and capsular polysaccharide both influence association of N. meningitidis with nasopharyngeal mucosa (Rayner et al, 1995 ;Stephens et al, 1993), but concurrent switching of multiple phase-variable bacterial surface components such as these, and outer-membrane proteins including Opa, appears to occur during successful invasion of this tissue (de Vries et al, 1996).…”
Section: -5246 # 2002 Sgmmentioning
confidence: 99%
“…Immunohistochemical analysis of tonsillar tissue from healthy carriers has demonstrated that colonizing meningococci can be found on the epithelial cell surface, in association with epithelial cells and in the tissue underlying the mucosal surface (42). The route of traversal has not been defined, although the bacterium has been detected in an intracellular compartment in epithelial cells (33,45,47).…”
mentioning
confidence: 99%
“…meningitidis is composed of various biologically active molecules, many of which are highly variable, most notably, OMP I1 (opacity 34-36 and pili (fimbriae).34,37*38 Pili are important adhesins in meningococci and isolates from patients are almost invariably pilate when observed microscopically. Pilation appears to be required for colonisation of host mucosal surfaces and for at least some stages of invasive disease caused by these bacteria.37, 39-43 Pili are filamentous protein appendages which extend considerable distances from the bacterial surface and are probably responsible for initial interaction with host epithelial cells and subsequently with endothelial cells.5, [42][43][44] Pili produced by pathogenic Neisseria spp. are composed of repeated subunits of pilin polypeptide with approximately 10 000 pilin subunits assembled to form an individual Meningococci have been observed to produce either one of two types of pilus, class I and class I1 (table II).576344346-52 Class I pili are The 53 N-terminal amino acids of mature pilin are conserved between antigenically distinct molecules constituting the conserved (C) region.…”
Section: Immunotype Ls-8 (B15 P1-4 Ls-8)mentioning
confidence: 99%